The Effect of Hexagon Fraud Theory on Financial Statement Fraud with Audit Committee As a Moderating Variable - Hasna, Dinda Aulia; Novianti, Nurlita (Association of Certified Fraud Examiners Indonesia Chapter, 2024)
Increased competition forces companies to prepare accurate financial statements. However, this situation also encourages unethical practices, such as financial reporting fraud or manipulation. By analyzing the audit committee’s function as a moderating variable, this study seeks to ascertain the impact of the notion of fraud on financial statement fraud. Six elements make up the theory: opportunity, pressure, capability, hubris, rationalization, and collusion. Financial statement fraud is quantified using the F-Score Model. Forty-three construction businesses that were listed on the Indonesia Stock Exchange between 2020 and 2022 are included in the sample. A component of the selection process was purposive sampling. Statistical Product and Service Solutions version 25 was used to process the results of the moderating regression analysis. The findings indicate that while opportunity, rationalization, and arrogance have little influence on financial statement fraud, cooperation does. On the other hand, capability and pressure have a beneficial impact. Furthermore, the audit committee does not regulate financial statement fraud via rationalization and arrogance; Rather, it does so through pressure, opportunity, capacity, and collaboration. Businesses should consider the factors that affect financial statement fraud detection, according to the study’s findings.